What was Killing Babies in Sundsvall? A Study of Infant Mortality Patterns Using Individual Level Cause of Death Data, 1860–1892 - Hiltunen Maltesdotter, Maria; Edvinsson, Sören (Historical Life Course Studies, 2025)
In this report, we analyse infant mortality in Sundsvall 1860–1892. The focus is on the pattern and development of causes of death with separate analyses of neonatal and post-neonatal mortality. Furthermore, we discuss the development of infant mortality in relation to possible determinants in the historical context in Sundsvall. The results show substantial differences between neonatal and post-neonatal mortality when it comes to causes of death as well as their seasonal pattern. For deaths in the first 28 days, a large proportion of the deaths were diagnosed as unknown disease or given vague and symptom-descriptive diagnoses. For post-neonatal mortality on the other hand, the dominant cause of death categories were water- and food-borne infections and air-borne infections. Water- and food-borne diseases had a very strong seasonal pattern with the peak in late summer — July and August. There is no indication that sanitary improvements in the 1880's led to fewer cases of diarrhoea. Mortality from air-borne diseases on the other hand was lowest during summer, instead peaking in the winter months.